The Invasion of Africa by European Migrants. The World Upside Down by Abdourahman A. Waberi - Cuche, François-Xavier (Sensus Historiae, 2025)
Waberi’s novel Aux États-Unis d’Afrique (2006) has been the subject of several articles, mainly devoted to the reversal in this fiction of the West’s current domination of Africa. Our hypothesis is that the theme of immigration is central to the book. Beyond the process of inversion, we will analyse the fictional African discourse on Western immigration, before making a generic study: neither utopia nor uchrony, the novel uses the figure of the world turned upside down to demonstrate the absurdity of essentialist discourse on human groups.